Operating systems : a spiral approach - Elmasri, R. Ramez Elmasri; Carrick, A. G. A. Gil Carrick; Levine, D. David Levine (Boston: McGraw Hill, 2010)
"Elmasri, Levine, and Carrick's "spiral approach" to teaching operating systems develops student understanding early and helps students approach the more difficult aspects of operating systems with confidence. While operating systems have changed dramatically over the years, the authors of most operating systems books use a linear approach that is difficult for students to follow and requires instructors to constantly put materials in context." "Elmasri, Levine, and Carrick do things differently by following an integrative or "spiral" approach to explaining operating systems. The spiral approach alleviates the need for an instructor to "jump ahead" when explaining processes by helping students "completely" understand a simple, working, functional system as a whole in the very beginning. It is also an effective pedagogically, and it inspires students to continue exploring more advanced concepts with confidence
Includes bibliography and index
Keywords: Operating Systems (Computers)